Food-borne disease outbreak of diarrhetic shellfish poisoning due to toxic mussel consumption: the first recorded outbreak in china. - Tingrui Chen (Public Library of Science (PLoS), 2013)
Objectives This investigation was undertaken in response to an outbreak of suspected shellfish poisoning in Zhejiang Province, China. The objectives of this project were to confirm the outbreak and to identify the aetiology, source and mode of transmission. Methods A probable case was defined as an individual with diarrhea (≥3 times/day) plus at least one of the following symptoms: fever (≥37.5°C), vomiting, or abdominal pain after consuming seafood between May 23(rd) and May 28(th), 2011. Using a case-control study design, we compared exposures to suspected seafood items and cooking methods between 61 probable cases and 61 controls. Results Over 220 suspected or probable cases of diarrhetic shellfish poisoning (DSP) were identified (incidence of 18 cases per 100,000). The case control study revealed that 100% of cases and 18% of controls had eaten mussels during the exposure period (OR = ∞, χ(2) = 84.72,P = 0.000). The number of mussels consumed was related to DSP risk (P = 0.004, χ2 test for trend). Consumption of other seafood items was not associated with disease. The frequency of diarrhea and vomiting were positively correlated with the number of mussels consumed (r = 0.424 and r = 0.562, respectively). The frequency of vomiting and the incubation period were significantly correlated with the total time the mussels were boiled (r = 0.594 and r = -0.336, respectively). Mussels from 3 food markets and one family contained Okadaic acid (OA) and Dinophysistoxin-1 (DTX-1). Conclusions This outbreak was attributed to the consumption of mussels contaminated by DSP-toxins (OA and DTX-1) which are produced by different species of dinoflagellates (toxic microalgae) from the genus Dinophysis or Prorocentrum. Suspension of mussel sales and early public announcements were highly effective in controlling the outbreak, although oversight of seafood quality should be a priority to prevent future contamination and outbreaks.